2016
DOI: 10.1177/0269216316639798
|View full text |Cite
|
Sign up to set email alerts
|

Turning waste medicines to cost savings: A pilot study on the feasibility of medication recycling as a solution to drug wastage

Abstract: Most donated medications were reusable. The current protocol can be further streamlined to focus on the more reusable donor sources and drug classes and validated in other settings. Overall, we opine that it is feasible to practise medication recycling on a larger scale to reduce medication wastage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…Redistributing the unused medications to those who need them may potentially reduce non-compliance and the associated healthcare costs. There was a pilot study on the feasibility of medication recycling, following certain protocols, as a solution to medication wastage conducted in Singapore (Toh & Chew 2016). This is a desirable practice and hospitals in Brunei have already practiced similar recycling through their in-patient pharmacies.…”
Section: Cost Saving From Medication Recyclingmentioning
confidence: 99%
“…Redistributing the unused medications to those who need them may potentially reduce non-compliance and the associated healthcare costs. There was a pilot study on the feasibility of medication recycling, following certain protocols, as a solution to medication wastage conducted in Singapore (Toh & Chew 2016). This is a desirable practice and hospitals in Brunei have already practiced similar recycling through their in-patient pharmacies.…”
Section: Cost Saving From Medication Recyclingmentioning
confidence: 99%
“…Previous research indicates that leftover antibiotics may contribute to inappropriate antibiotic consumption hence further promoting antibiotic resistance . Drug waste may also contribute to antibiotic resistance and raise healthcare cost . Considering the prevalence of H pylori infection, arguments and the complexity for its treatment, poor accordance of registered drug packs or poor patient adherence to the treatment may contribute to antibiotic resistance and healthcare costs.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of medications that was theoretically eligible for redispensing is similar to that reported by others [ 9 , 29 ]. One study found that more than 90% of returned medications were eligible for redispensing, but this study did not apply the criterion that the original outer package must be unopened and intact [ 30 ]. However, none of those studies examined determinants of returned medications that are eligible for redispensing.…”
Section: Discussionmentioning
confidence: 99%